Makna Dīn dalam Al-Qur’an - Khoirur Rifqi Robiansyah (Fakultas Ushuluddin dan Dakwah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2024)
This article attempts to examine the meaning of the word din found in surah al-Kafirun: 6 as a reflection of the debate regarding the limits of official religion criteria in the state. The author uses Roland Barthes' semiotic approach in analyzing the meaning of the word din by looking at the denotation aspect as a linguistic system and the connotation aspect as a mythological system. This study uses a qualitative method. The results of the study are on the linguistic system of words that have a religious meaning. Then, in the mythological system, the word din means the religion of the Quraysh infidels who only have the concept of polytheism and worship rituals. They do not have the concept of prophets and scriptures. This finding shows that the Qur'an is even more inclusive in providing the construction of criteria for religious boundaries. Implicitly, Surah al-Kafirun verse 6 conveys the message of an ideology of tolerance and egalitarianism.